Assessment of Proximate and Phytochemical contents of Some Herbal Snuffs Sold in Sokoto Metropolis, Nigeria - Ummu Tukur; AI Umar; Sarkingobir, Yusuf; Ahmad Zayyanu (Indonesian Chimica Letters, 2023)
There is current rise in use of herbal stuffs for medicinal purposes due to accessibility, cheapness, and other reasons. But information about their contents is limited and therefore it is imperative to unveil it.  The objective of this work was to carry out determination of phytochemicals, and proximate compositions of the selected herbal snuffs in Sokoto, Nigeria.The three different herbal snuffs namely, Hajiya Aisha, Hajiya safiya, and Dr Lambo were purchased from Sokoto market, Sokoto City, Sokoto State, Nigeria. The determination of phytochemicals, and proximate compositions was performed by the methods of Association of Analytical Chemists. Alkaloids, tannins, flavonoids, cardiac glycosides, glycosides steroids, and terpenoids were determined. In terms of ash, the range determined is 23.00 ± 0.05 to 25.00±0.1 %. The lipid assessed was 9.10 ± 0.5 to 13.00 ± 0.05 %. 5.00 ± 0.3 to 8.20± 0.02 % was the range of protein determined. Fibre values of 6.60 ± 0.02 to 10.10± 0.5 % were reveled and 41.00 ± 0.1 to 48.10 ± 0.5 % is the range of carbohydrate assessed in the snuffs. Nevertheless, owing to the nutritional proximate values, and medicinally useful phytochemicals determined in these snuffs (Dr Lambo, Hajiya Aisha, and Hajiya Safiya) selected from sokoto, Nigeria; the snuffs are of benefits to the users in that regards. However, other scientific quality measurement studies should be done to ascertain the safety of the snuffs on human subjects.